Nasser Khosrow and Sanai Poets of Bipolar or Multipolar? (Poetic awakening from dream to reality) - Nusrat Fatemi, Seyedeh (2021)
Different views have long been expressed about poetry, its essence and purpose. Poetry and the environment, together, are constantly changing and being influenced by each other. Poetry as a social necessity has always been a tool to promote worldly and spiritual purposes. Nasser Khosrow and Sanai, bipolar poets whose dark thoughts and ideas could not be found in the dark pole of their poetry and thought, and as a result of their inner intellectual and revolutionary awakening, marked a turning point in the history of culture and literature of this rich border. They figured out and made the poem, which they had previously employed in their worldly needs and lowly interests, as a means of spreading morality and religion, and they were epoch-making. Regardless of some of the intellectual contradictions that result from going through different mental states, their poetry has been a mirror of their society's pain and aspirations. This study, while explaining the characteristics of good and committed poetry and its mission, deals with the subject of intellectual awakening, its causes and contexts in the poetry and thought of these two poets, and examines the effect of this awakening on their intellectual orientation, whether it is possible between dark and light poles. Their thought was absolutely different, or this demarcation - in terms of their intellectual contradictions - is merely the result of views based on prejudice, absolutism and sanctification.